Women and girls in resource poor countries experience much greater exposure to household air pollutants than men: Results from Uganda and Ethiopia. (October 2018) - Okello, Gabriel; Devereux, Graham; Semple, Sean
Abstract: Household Air Pollution (HAP) from burning biomass fuels is a major cause of mortality and morbidity in low-income settings worldwide. Little is known about the differences in objective personal HAP exposure by age and gender. We measured personal exposure to HAP across six groups defined by age and gender (young children, young males, young females, adult males, adult females, and elderly) in rural households in two sub-Saharan African countries. Data on 24-hour personal exposure to HAP were collected from 215 participants from 85 households in Uganda and Ethiopia. HAP exposure was assessed by measuring carbon monoxide (CO) and/or fine particulate matter (PM2.5 ) concentrations using five types of devices. 24 h PM2.5 personal exposure was highest among adult females with Geometric Mean (GM) and Geometric Standard Deviation (GSD) concentrations of 205 μg/m 3 (1.67) in Ethiopia; 177 μg/m 3 (1.61 GSD) in Uganda. The lowest PM2.5 exposures were recorded among young males GM (GSD) 30.2 μg/m 3 (1.89) in Ethiopia; 26.3 μg/m 3 (1.48) in Uganda. Young females had exposures about two-thirds of the adult female group. Adult males, young children and the elderly experienced lower exposures reflecting their limited involvement in cooking. There was a similar pattern of exposure by age and gender in both countries and when assessed by CO measurement. There are substantial differences in exposure to HAP depending on age and gender in sub-Saharan Africa rural households reflecting differences in household cooking activity and time spent indoors. Future work should consider these differences when implementing exposure reduction interventions. There was a strong agreement between optical and gravimetric devices measurements although optical devices tended to overestimate exposure. There is need to calibrate optical devices against a gravimetric standard prior to quantifying exposure. Highlights: First study in sub-Saharan Africa to examine differences in exposure to Household Air Pollution by age and gender 24h personal exposure measurement for PM2.5 and CO conducted in rural sub-Saharan Africa settings Comparison of measurements from optical and gravimetric devices Women and girls experience much higher household air pollutant exposures than men and boys